Does Tax Amnesty Program Reduce Cross-Border Tax Evasion? A Case Study in Indonesia - Arnaldo Purba; Darmawan Mangkan; Andrey Hasiholan Pulungan (Journal of Business & Applied Management, 2022)
Prior to the implementation of automatic exchange of information (AEOI), Indonesian government introduced tax amnesty program in 2016 by providing taxpayers with an opportunity to correct their annual tax returns that were previously reported not based on actual condition. This paper attempts to empirically measure the impact of the tax amnesty program on cross-border tax evasion in Indonesia by using changes in deposits owned by Indonesian residents kept in banks located in offshore jurisdictions, or known as cross-border deposits, to proxy for cross-border evasion. Quarterly data on cross-border deposits was obtained from Bank for International Settlement (BIS) Locational Banking Statistics (LBS) from third quarter 2016 until fourth quarter 2017. Using difference-in-difference analysis, our study finds insufficient evidence to suggest that cross-border tax evasion in Indonesia is impacted by the amnesty program. The results also indicate that the government may need to more effectively use the AEOI data received from its partners to investigate whether the taxpayers still commit cross-border tax evasion by hiding their financial assets in offshore financial institutions. This study contributes to academic literature by extending tax literature, specifically about tax evasion and tax amnesty. It also provides insights to regulator about the relationship between tax amnesty and cross-border tax evasion.